POLA KOMUNIKASI ANTAR ANGGOTA KOMUNITAS ANAK PUNK DI KOTA CURUP KABUPATEN REJANG LEBONG - Hendi Septiadi; Vethy Octaviani; Antonio Imanda (Professional: Jurnal Komunikasi dan Administrasi Publik, 2016)
This study aimed to determine the communication patterns between punk community member in Curup Rejang Lebong. This study used qualitative research methods, with descriptive research approach. Informants in this study were four members of the punk community. Data collection techniques used by researchers were observation, interviews and documentation. The results showed that the patterns of communication used by members of punk were: one-way communication pattern, two-way communication pattern, and multidirectional communication pattern. In the pattern of one-way communication, punk community members act as listeners or communication made in the form of instructions through mobile media (handphone). This two-way communication patterns better clarify the pattern of one-way communication where the causal direction alternates for their feedback whether the message could be understood and accepted. Multidirectional communication patterns occur in this community go well, because here they exchange ideas or discuss and receive advice among fellow community through consultation conducted every month to pull out the ideas that could be useful for the progress of the punk community members and strengthen the relationships between community members.